FAKTOR YANG BERHUBUNGAN DENGAN KESEDIAAN MASYARAKAT MENERIMA VAKSINASI COVID-19 DI WILAYAH KERJA PUSKESMAS KULATI KABUPATEN WAKATOBI TAHUN 2021 - Dhiya Ramadhani; Jumakil Jumakil; jafriati jafriati; Irma Irma (Endemis Journal, 2022)
Indonesia and other countries are still struggling to overcome the Covid-19 pandemic. To date, there have been more than 4 million confirmed cases of Covid-19 in Indonesia. Various control efforts continue to be carried out, one of which is through the implementation of the Covid-19 vaccination. However, there are still many people who are reluctant to receive the Covid-19 vaccination, this is due to several factors such as lack of knowledge and people still do not believe in the Covid-19 vaccine.. This study aims to factors related to community willingness to receive covid- 19 vaccination in the working area of the Kulati health center Wakatobi regency in 2021. This research method uses an analytic observational research type with a cross sectional approach and the sampling technique uses proportionate stratified random sampling. The results showed that of the 321 respondents who were willing to receive the Covid-19 vaccination, 130 (40.5%) respondents and 191 (59.5%) respondents who were not willing to receive the Covid-19 vaccination. Based on the bivariate analysis, it was obtained knowledge (p value = 0.000), perception (p value = 0.000), and location affordability (p value = 0.115). The results of the study can be concluded that there is a relationship between knowledge and perception with the willingness of the community to receive the Covid-19 vaccination, while there is no relationship between the affordability of the location and the willingness of the community to receive the Covid-19 vaccination.